The International English Language Testing System (IELTS): A Critical Review - Peltekov, Peter (Yayasan Visi Intan Permata, 2021)
Considering the increasing popularity of the International English Language Testing System (IELTS), the present article provides a succinct description and critique of the test. As with any high-stakes assessment, educational institutions need to carefully examine all aspects of a given assessment tool before applying it in practice. Green’s (2014) framework for the evaluation of second language assessment tools was applied to the analysis of the IELTS test. The present review demonstrated that there are many ways in which the IELTS test can be improved (e.g., increasing the authenticity of the listening modules and reducing the role of construct irrelevant skills). While it is far from flawless and not the only option, IELTS continues to be one of the most popular international tests of English language proficiency. Clearly, the test is an important gate-keeping measure and an incentive for millions of non-native speakers to improve their English language skills. As we know, the beneficial consequences of a given assessment system are on the top of the hierarchy of effective assessment characteristics (Green, 2014), and IELTS seems to achieve its purpose. However, it is hoped that the present critical review is a valuable contribution to the ongoing validation and improvement of the test. At the very least, it is hoped that it would help assessment stakeholders to better understand the structure of the test and to reflect on its usefulness in a more informed and objective way.